Chebyshev's inequality application in queues domain tail distributions upper bound calculation - Ferreira, Manuel Alberto M. (2014)
In the countless queues applications, and related quantities, the distribution functions are of great importance. This is because only they allow the interesting probabilities determination. Often practical expressions are difficult to obtain. In this work two situations for which upper bounds tail distributions are obtained, through Chebyshev’s inequality, are presented.